(untitled) (Third Sector Social Economic Review, 2022)
The unified theory of acceptance and use of technology has been cited more than 40000 by numerous studies since its emergence. However, no detailed research has yet been conducted to analyze and compare the reasons for citing reference articles in detail. For this reason, this model, which is getting more interesting, should be examined in detail. In this context, bibliometric analysis and mapping methods were used to systematically examine a total of 1560 studies related to UTAUT. With these data, general citation trends, application areas, journals, countries, institutions, and authors with the most studies were analyzed. In this way, the effectiveness of these titles has been revealed. After that, terms were extracted from the keywords. Hence, effective terms and titles in the field were obtained. The findings are shown with visuals and tables to increase intelligibility. Thus, a structure was created that everyone can easily understand. Such a systematic review of the UTAUT model can inform researchers and guide the appropriate future use of these theories. In study, a detailed examination of this model is presented and information about its scope is given.